EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TGT BERBASIS ASSESMENT FOR LEARNING (AfL) DITINJAU DARI GAYA KOGNITIF SISWA - Ilham Rais A; Mardiyana Mardiyana; Budi Usodo (Jurnal Pembelajaran Matematika, 2013)
Abstract: The aims of this research were to investigate: (1) which learning model of the cooperative learning model of the AfL-based TGT type, that of TGT, and the conventional learning model results in a better learning achievement; (2) which cognitive style type of the field dependent and the field independent results in a better learning achievement; (3) in each learning model (the cooperative learning model of the AfL-based TGT type, that of TGT, and the conventional learning model) which cognitive style results in a better learning achievement; and (4) in each cognitive style type (the field independent  and the field dependent), which learning model results in a better learning achievement. This research used the quasi experimental research method. The samples of the research consisted of 302 students. The instruments consisted of the test of learning achievement and cognitive style. The data was analyzed using the unbalanced two- way analysis of variance. The results of the research were as follows: (1) the cooperative learning model of the AfL-based TGT type results in a better learning achievement than that of the TGT type or the conventional learning model, and the cooperative learning model of the TGT type results in a better learning achievement than the conventional learning model; (2) the students with the cognitive style of the field independent has a better learning achievement than those with the cognitive style of the field dependent; (3) in that each learning model, the students with the cognitive style of the field independent have a better learning achievement than those with the cognitive style of the field dependent; and (4) in that each cognitive style, the cooperative learning model of the AfL-based TGT results in a better learning achievement than that of the TGT type or the conventional learning model, and the conventional learning of the TGT type results in a better learning achievement than the conventional learning model. Key words: TGT, AfL, Cognitive Style, and Learning Achievement.